Digital Leg Volume Quantification: Precision Assessment of a Novel Workflow Based on Single Capture Three-dimensional Whole-Body Surface Imaging. - Etzel, Lucas; Schenck, Thilo L.; Giunta, Riccardo E.; Li, Zhouxiao; Xu, Ya; Koban, Konstantin C. (Journal of Digital Imaging, 2021)
Whole-body three-dimensional surface imaging (3DSI) offers the ability to monitor morphologic changes in multiple areas without the need to individually scan every anatomical region of interest. One area of application is the digital quantification of leg volume. Certain types of morphology do not permit complete circumferential scan of the leg surface. A workflow capable of precisely estimating the missing data is therefore required. We thus aimed to describe and apply a novel workflow to collect bilateral leg volume measurements from whole-body 3D surface scans regardless of leg morphology and to assess workflow precision. For each study participant, whole-body 3DSI was conducted twice successively in a single session with subject repositioning between scans. Paired samples of bilateral leg volume were calculated from the 3D surface data, with workflow variations for complete and limited leg surface visibility. Workflow precision was assessed by calculating the relative percent differences between repeated leg volumes. A total of 82 subjects were included in this study. The mean relative differences between paired left and right leg volumes were 0.73 ± 0.62% and 0.82 ± 0.65%. The workflow variations for completely and partially visible leg surfaces yielded similarly low values. The workflow examined in this study provides a precise method to digitally monitor leg volume regardless of leg morphology. It could aid in objectively comparing medical treatment options of the leg in a clinical setting. Whole-body scans acquired using the described 3DSI routine may allow simultaneous assessment of other changes in body morphology after further validation.